Polysaccharides as Edible Films and Coatings: Characteristics and Influence on Fruit and Vegetable Quality—A Review - Kocira, Anna; Kozłowicz, Katarzyna; Panasiewicz, Katarzyna; Staniak, Mariola; Szpunar-Krok, Ewa; Hortyńska, Paulina (Agronomy (Basel), 2021)
There has been a significant increase in the development of edible films and coatings in recent times, and this is expected to have a significant impact on the quality of fruit and vegetables in the coming years. Consumers expect fresh fruit and vegetables free from pesticide residues, with high quality, nutritional value and an extended shelf life. The application of coatings and edible films to fruits and vegetables represents an environmentally friendly approach to an innovative solution to this problem. Coatings and edible films can act as ecological and biodegradable packaging. The coating strategy involves a combination of natural biopolymers and appropriate preservation methods. The article presents the applicability, trends and perspectives of polysaccharide coatings and edible films and their impact on the quality of fruit and vegetables, providing an understanding of their main functions and benefits. Numerous studies show that natural polysaccharides are well suited for use as packaging material for fresh fruit and vegetables and can often be an important alternative to synthetic compounds. Natural polymer materials are a good barrier to oxygen and carbon dioxide; however, they are characterised by excessive solubility in the water environment, water vapour permeability and low extensibility. The properties of edible coatings can be modified by the addition of plasticisers, surfactants, cross-linkers, antimicrobial agents, functional additives, nanosilver particles or fruit and vegetable residues. The use of an electric field is also a promising technology here. The use of polysaccharides for the preparation of edible films and coatings is justified not only by the possibility of reducing the consumption of packaging made of synthetic polymer materials but also by the fact that the production of some natural polymers can be made using waste products generated during the processing of food raw materials.